2000
DOI: 10.1074/jbc.275.13.9476
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Mechanism of 3-Deoxy-d-manno-octulosonate 8-Phosphate Synthase

Abstract: 3-Deoxy-D-manno-octulosonate 8-phosphate (KDO8P) synthase catalyzes the condensation of phosphoenolpyruvate (PEP) with arabinose 5-phosphate (A5P) to form KDO8P and inorganic phosphate. KDO8P is the phosphorylated precursor of 3-deoxy-D-manno-octulosonate, an essential sugar of the lipopolysaccharide of Gram-negative bacteria. The crystal structure of the Escherichia coli KDO8P synthase has been determined by multiple wavelength anomalous diffraction and the model has been refined to 2.4 Å (R-factor, 19.9%; R-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
138
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(150 citation statements)
references
References 42 publications
9
138
3
Order By: Relevance
“…5). The determination of the crystal structure of E. coli Kdo-8-P synthase provided information on the threedimensional organization of the bacterial enzyme subunit, the interactions between subunits, the conformation of active sites, and the mechanism for the catalyzed reaction (Radaev et al, 2000;Wagner et al, 2000;Asojo et al, 2001). Mutations in the putative binding sites for the substrates totally inactivate (R61/T62 for binding of Ara-5-P) or greatly affect the enzyme activity (K136 for binding of PEP).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5). The determination of the crystal structure of E. coli Kdo-8-P synthase provided information on the threedimensional organization of the bacterial enzyme subunit, the interactions between subunits, the conformation of active sites, and the mechanism for the catalyzed reaction (Radaev et al, 2000;Wagner et al, 2000;Asojo et al, 2001). Mutations in the putative binding sites for the substrates totally inactivate (R61/T62 for binding of Ara-5-P) or greatly affect the enzyme activity (K136 for binding of PEP).…”
Section: Discussionmentioning
confidence: 99%
“…The amino acid residues shown to be essential for E. coli Kdo-8-P synthase activity (Salleh et al, 1996;Sheflyan et al, 1999;Radaev et al, 2000) are conserved in the sequence of the plant enzymes as shown in Figure 1. In the tomato Kdo-8-P synthase, residue K136 may be involved in the binding of PEP, residues R61 and T62 may be involved in the binding of Ara-5-P, and residues C164, H198, and H242 may represent structurally important residues for maintenance of active sites.…”
Section: Site-directed Mutagenesis Of the Tomato Kdo-8-p Synthasementioning
confidence: 99%
See 1 more Smart Citation
“…2). Results from inhibition studies with both cyclic and acyclic product analogues (15, 16) have failed to differentiate between these mechanisms, and although no direct evidence exists, a recent structure determination favors the linear intermediate (17).In contrast to the numerous phenotypic studies on temperature-sensitive S. typhimurium mutants, and despite the prominent role of these experiments in rationalizing the study of KDO8P synthase and the wealth of knowledge concerning Escherichia coli KDO8P synthase, the nature of the S. typhimurium KDO8P synthase mutation at the enzymatic level has never been investigated. S. typhimurium AG701i50 is unable to grow at 42°C and has been used in complementation experiments to identify KDO8P synthase activity encoded in DNA libraries (18 -20).…”
mentioning
confidence: 99%
“…1) (12,13). The first committed step to KDO generation is catalyzed by 3-deoxy-D-manno-octulosonate 8-phosphate (KDO 8-P) synthase, which condenses D-arabinose 5-phosphate (A5P) with phosphoenolpyruvate via a stereospecific aldol-type condensation (14,15). A5P is the first intermediate unique to the KDO biosynthetic pathway, and API is the main de novo source of A5P in Gram-negative bacteria, because it is not readily available via glycolysis (16).…”
mentioning
confidence: 99%